Evaluation of Phytochemicals from Malbranchea cinnamomea, a thermophilic fungi isolated from compost (vegetable waste compost) - M, Geetha. (International Journal of Scientific Research in Biological Sciences, 2018)
The study was conducted at Department of Botany, Bangalore University, Bengaluru. Vegetable wastes are created during harvesting, transportation, storage, marketing and processing. The mixed vegetable waste were collected from different markets and then composted in heaps and pits. Composting was done during the year 2013. The temperature of the compost were recorded and then the soil samples were collected during thermophilic stage in polythene bags and bought to the laboratory. Isolation was done on Potato Dextrose Agar media (PDA) following serial dilution method and cultures were purified on PDA. The present study was carried out to evaluate the presence of phytochemicals from the isolated thermophilic fungi namely Malbranchea cinnamomea. Then the phytochemicals like totalphenols and flavonoids were estimated or analysed both qualitatively and quantitatively following standard procedure. In conclusion, the culture filtrate of Malbranchea cinnamomea has an ability to produce the phytochemicals. Among the phytochemicals the total phenols was maximum than tannins and flavonoids.